The healing properties of essential oil / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2024)
Have you heard about essential oil (EO) in Malaysia in the good old days ? It would have been used in small quantities by various groups of people before the 21st century but it was not commercialized . Today , EOs are widely used in the country and there are many brands in the market, to name a few - Young Living, doTERRA, Easecox . I am not promoting the brands of EOs here, but generally they have benefitted many people across the globe .EO is not something new in the 21st century . Historically, the use of essential oil started way back in 4500 B.C.E by the Egyptians. It was used to create tinctures, powders, salves and ointments for medical purposes and spiritual ceremonies . In China , the use of essential oil was also practised by The Yellow Emperor, Huang Di during his reign in 2597 BC.